Behavioral responses to resource heterogeneity can accelerate biological invasions. Issue 5 (May 2017) - Lutscher, Frithjof; Musgrave, Jeffrey A.
Abstract: The abundance and spatial distribution of resources in a landscape and the behavioral response of individuals determines whether and how fast an invasive species spreads in an environment. Whether and how landscape manipulations can be used to slow invasive species is of great interest, in particular in forest ecosystems, where tree removal, thinning, and increasing tree diversity are discussed as management options. Classically, the focus is on availability and accessibility of resources; more recent considerations include individual‐level behavioral movement responses to a spatially heterogeneous resource distribution. We derive a novel model for insect–host dynamics that includes three common behavioral aspects of foraging: higher movement rate in resource‐poor areas, lower ovipositioning rate in resource‐poor areas, and movement preference for resource‐rich areas. We show that each of these basic mechanisms can increase the speed of invasion in a source–sink landscape above that in a homogeneous landscape with larger overall resource availability. We parameterize our model and illustrate our results with data for emerald ash borer, a recent highly destructive forest pest in North America. Our results highlight the importance of empirical work on movement behavior in different landscape types and near the interface between types.